A MISMATCH OF IDEALS: THE AILS OF ENGLISH EDUCATION POLICY IN SOUTH KOREA: Received: 2nd May 2022; Revised: 3rd June 2022, 6th June 2022, 24th June 2022; Accepted: 7th October 2022 - Simon, Michael P (PUPIL: International Journal of Teaching, Education and Learning, 2022)
Despite several modifications in English education policy over many years in South Korea, there seems to be no discernable improvement in language ability. This problem has been investigated empirically by researchers domestically and internationally, with no consensus as to the underlying issue. This paper attempts to pivot the discussion to a more philosophical position by approaching the issue from a policy viewpoint. The overall aims of education, foreign language learning aims, as well as South Korea’s relationship with English education is examined. The fundamental concern is the mismatch between how society views English to how English education policy is enacted. Specific suggestions are then made regarding the ways in which policy makers can adjust their approaches to meet the needs of societal expectations of English proficiency. It is hoped that from a narrowing of insight from the macro-view of education at large to the specific problem in Korea will lead to changes in policy for the better.